Partisanship and selective reporting in Nigerian newspapers’ coverage of elections (2018)
This study examined the level of objectivity demonstrated by Nigerian newspapers in their coverage of elections with specific reference to the Nigeria‘s 2015 presidential election. Textual analysis was used to examine news stories about electioneering activities of the two leading political parties—the People‘s Democratic Party (PDP) and the All Progressives Congress (APC)—as reported by The Nation, Nigerian Tribune, The Punch and Vanguard newspapers, which were selected purposively based on their national reach and ownership. The newspapers foregrounded some news stories about the political parties and their presidential candidates while they buried others in manners that reflected biases influenced by ownership and political alignments of the newspapers. This trend has implications for Nigeria‘s democracy as the frames adopted by the news media to report electioneering activities may determine the voting decisions of the electorate and the final outcome of elections. Therefore, Nigerian news media should be fair and objective while reporting sensitive issues such as elections.